Heat treatment of Sodium Hypochlorite : A Comprehensive Review - Saurabh Rathi; Pradnya Nikhade; Manoj Chandak; Anuja Ikhar; Nidhi Motwani; Meghana Deshpande; Madhulika Chandak (Institute of Medico-legal Publications Pvt Ltd, 2021)
Introduction - The primary objective of root canal therapy is reduction of the bacteria in the root canal. Theeffective debridement depends on thorough cleaning and shaping of the complex root canal system. Chemicaldébridements can be optimally achieved using various irrigants and intracanal medicaments. The primaryirrigant of choice is Sodium Hypochlorite. It has excellent tissue dissolving ability along with antibacterialproperty. The purpose of this review is to discuss the need to heat Sodium Hypochlorite, techniques to heatSodium Hypochlorite, effect of Sodium Hypochlorite on tissue dissolution, antibacterial efficacy, penetrationinto dentinal tubules, viscosity, and effect on Ni-Ti alloy and temperature rise on external surface of root.Method- An electronic search was carried out using the certain keywords: “sodium hypochlorite”, “heatedsodium hypochlorite”, “prewarmed sodium hypochlorite”, “intracanal heating of sodium hypochlorite”, tocollect literature available on Heat treatment of Sodium hypochlorite.Result- Fourty One articles published between 1936-2020 were selected. Four main categories of data werehighlighted: Sodium Hypochlorite and Heat, the need to heat Sodium Hypochlorite, different techniques toHeat Sodium Hypochlorite, effect of Sodium Hypochlorite on various parameters.Conclusion- The efficacy of lower concentration of sodium hypochlorite can be effectively enhanced byincreasing its temperature. It enhance the pulp dissolution, antibacterial efficacy and flow without anyadverse effect on periodontal ligament or outer surface of the root.